2005
DOI: 10.1212/01.wnl.0000183702.04080.27
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis in stroke patients aged 80 years and older: Swiss survey of IV thrombolysis

Abstract: This databank-based, multicenter study compared all stroke patients with IV tissue plasminogen activator aged > or = 80 years (n = 38) and those < 80 years old (n = 287). Three-month mortality was higher in older patients. Favorable outcome (modified Rankin scale < or = 1) and intracranial hemorrhage (asymptomatic/symptomatic/fatal) were similarly frequent in both groups. Logistic regression showed that stroke severity, time to thrombolysis, glucose level, and history of coronary heart disease independently pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
88
2
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 8 publications
11
88
2
5
Order By: Relevance
“…These mortality rates were lower for both age groups than those reported in previous studies, with the North American Solitaire Stent Retriever Acute Stroke (NASA) registry reporting 27.3% 90-day mortality in the younger group and 43.9% in the older group. 12 Most interesting, Engelter et al 9 in their analysis of IV thrombolysis and Mono et al 10 in their analysis of intra-arterial thrombolysis reported lower rates of 90-day mortality compared with the NASA registry, with 12% and 22% mortality for younger cohorts, respectively, and 32% and 40% mortality in the older cohorts. The Engelter and Mono studies reviewed results using treatment methods with lower recanalization rates than stent retrievers, and the NASA registry had an older patient population.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These mortality rates were lower for both age groups than those reported in previous studies, with the North American Solitaire Stent Retriever Acute Stroke (NASA) registry reporting 27.3% 90-day mortality in the younger group and 43.9% in the older group. 12 Most interesting, Engelter et al 9 in their analysis of IV thrombolysis and Mono et al 10 in their analysis of intra-arterial thrombolysis reported lower rates of 90-day mortality compared with the NASA registry, with 12% and 22% mortality for younger cohorts, respectively, and 32% and 40% mortality in the older cohorts. The Engelter and Mono studies reviewed results using treatment methods with lower recanalization rates than stent retrievers, and the NASA registry had an older patient population.…”
Section: Discussionmentioning
confidence: 98%
“…[6][7][8] However, it has been reported in multiple studies that despite similar rates of recanalization, the elderly have higher mortality rates and poorer outcomes than younger patients following intra-arterial treatment. 7,[9][10][11][12][13] These studies were mostly retrospective, single-center series or used older generation devices with suboptimal reperfusion rates. 7,[9][10][11][12][13] Recent clinical studies demonstrating the value of mechanical thrombectomy for acute ischemic stroke (AIS) did not include a significant number of elderly patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9] Observational studies comparing patients aged with respect to the effect of intravenous (IV) or intra-arterial (IA) thrombolysis. [10][11][12][13][14][15] Most of studies showed that the elderly treated with thrombolysis have higher mortality than the younger, and they tend to have worse outcome. The risk of symptomatic hemorrhagic transformation (sHT) is not different between the elderly and younger patients, although there are persistent concerns that advanced age increases the risk of sHT related to thrombolysis, 11,12,16,17 By including only the patients received thrombolysis, most of previous studies made a comparison between the old, thrombolysis-treated patients and the young, also thrombolysis-treated ones.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] Most of studies showed that the elderly treated with thrombolysis have higher mortality than the younger, and they tend to have worse outcome. The risk of symptomatic hemorrhagic transformation (sHT) is not different between the elderly and younger patients, although there are persistent concerns that advanced age increases the risk of sHT related to thrombolysis, 11,12,16,17 By including only the patients received thrombolysis, most of previous studies made a comparison between the old, thrombolysis-treated patients and the young, also thrombolysis-treated ones. Because the elderly patients have more disabling stroke and an increased mortality across a similar spectrum of stroke severity, 1,18 it is natural that we expect worse outcome in the elderly compared to the younger when both are treated with thrombolysis.…”
Section: Introductionmentioning
confidence: 99%